(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The ability to form biofilms by microorganisms is one of the virulence factors used by bacteria to cause disease and is measured by measuring optical density (O.D), which is a measure to estimate the concentration of bacterial species growing in the culture media. Materials and Methods: The bacterial cultures of six different bacterial isolates of S. marcescens and Klebsilla pnemoniae , Enterococcus cloacea , Eshcherchia coli , Staphylococcus aureus, Psedomonas aeruginosa were reconstituted from frozen stock, which diagnosed by using VITEK 2 Densi screening tool, then plant extracts of Allium sativum and Alhagi maurorum were prepared to test the effect of these extracts on the bacterial isolates under study.Optical density was measured using a spectrophotometer at a wavelength of 490 nm before and after treatment of the bacterial isolates with the two extracts A.sativum and A. maurorum . Results: The ability of K. pnemoniae , S. marcescens and E. cloacea, to form biofilm reduced with absorption value 0.52±0.01, 0.66±0.03, 0.8±0.01 respectively, and the ability to form biofilm from E. cloacea , E. coli after adding A. maurorum extract was decreased and the absorbance value reached 0.66±0.01,0.66±0.005 respectively after being treated with A. maurorum extract. Conclusion: Biofilm formation is one of the virulence factors that helps microorganisms resist the environment in which they exist and resist antibiotics. Therefore, medicinal plant extracts are used as an alternative, which have been shown to inhibit the growth of some pathogenic bacterial species.